Proceedings of the Third International Scientific Conference “Intelligent Information Technologies for Industry” (IITI’18) Volume 2 - Abraham, Ajith; Kovalev, Sergey; Tarassov, Valery; Snasel, Vaclav; Sukhanov, Andrey (Advances in Intelligent Systems and Computing, 2019)
XV, 450 p. 164 illus.